Pelagiphages in the Podoviridae family integrate into host genomes. (19th December 2018) - Zhao, Yanlin; Qin, Fang; Zhang, Rui; Giovannoni, Stephen J.; Zhang, Zefeng; Sun, Jing; Du, Sen; Rensing, Christopher
Summary: The Pelagibacterales order (SAR11) in Alphaproteobacteria dominates marine surface bacterioplankton communities, where it plays a key role in carbon and nutrient cycling. SAR11 phages, known as pelagiphages, are among the most abundant phages in the ocean. Four pelagiphages that infect Pelagibacter HTCC1062 have been reported. Here, we report 11 new pelagiphages in the Podoviridae family. Comparative genomics classified these pelagiphages into the HTVC019Pvirus genus, which includes the previously reported pelagiphages HTVC011P and HTVC019P. Phylogenomic analysis clustered HTVC019Pvirus pelagiphages into three subgroups. Integrases were identified in all but one HTVC019Pvirus genome. Site‐specific integration of HTVC019Pvirus pelagiphages into host tRNA genes was verified experimentally, demonstrating the capacity of these pelagiphages to propagate by both lytic and lysogenic infection. Evidence of pelagiphage integration was also retrieved from the Global Ocean Survey database, showing that prophages are found in natural SAR11 populations. HTVC019Pvirus pelagiphages could impact SAR11 populations by a variety of mechanisms, including mortality, genetic transduction and prophage‐induced viral immunity. HTVC019Pvirus pelagiphages are a rare example of cultured lysogenic phage that can be implicated in ecological processes on broad scales. These pelagiphages have the potential to become a useful model for investigating strategies of host infection and phage‐dependent horizontal gene transfer.